anonymous
  • anonymous
Anyone good with solving by elimination?
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
schrodinger
  • schrodinger
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
pooja195
  • pooja195
Post the question
anonymous
  • anonymous
2m=-4n-4 3m+5n=-3
Vocaloid
  • Vocaloid
start by rewriting the first equation to match the format of the second equation 2m + 4n = -4 3m + 5n = -3 start by multiplying the first equation by 3 and tell me what you get

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
6+12=-12
Vocaloid
  • Vocaloid
don't forget the variables, those are important
Vocaloid
  • Vocaloid
6m + 12n = -12
Vocaloid
  • Vocaloid
now multiply the second equation by (-2)
anonymous
  • anonymous
ok -6m+-10n=-6
Vocaloid
  • Vocaloid
almost, should be positive 6 at the end
anonymous
  • anonymous
oh yes sorry
Vocaloid
  • Vocaloid
so we have 6m + 12n = -12 -6m - 10n = 6 now add the two equations together
anonymous
  • anonymous
0m+2n=-6
Vocaloid
  • Vocaloid
good, so n = ?
anonymous
  • anonymous
-3
Vocaloid
  • Vocaloid
good. so, we can take one of the equations 2m + 4n = -4 and plug in n to solve for m 2m + 4(-3) = -4 m = ?
anonymous
  • anonymous
-2?
Vocaloid
  • Vocaloid
not quite 2m - 12 = -4 2m = 8 m = ?
anonymous
  • anonymous
4
Vocaloid
  • Vocaloid
good, so m = 4 and n = -3, and that's our solution
anonymous
  • anonymous
You're the best , thank you

Looking for something else?

Not the answer you are looking for? Search for more explanations.